Worldwide meta-analysis of the prevalence of Campylobacter in animal food products - Zbrun, María Virginia (2020)
The objective of this meta-analysis was to summarize available information on the prevalence of thermotolerant Campylobacter in different animal food products. A number of multilevel random-effect meta-analysis models were fitted to estimate mean prevalence of thermotolerant Campylobacter and to compare them among animal food products (cattle, pigs, broiler, hen, goat, sheep). The mean prevalence of Campylobacter spp. in animal food products was 29.6% (95% CI 27.6%–31%), and the mean prevalence of C. jejuni and C. coli were 19.3% and 9.7%, respectively. The prevalence of Campylobacter spp. was higher in products whose sources were broiler meat (p-estimate = 47.8%; 95% CI 44.9%–50.6%). C. jejuni was mainly observed in broiler meat where prevalence estimate (p-estimate) was 33.7% (95% CI 30.7%–36.8%). On the other hand, C. coli was observed in broiler meat (p-estimate = 14.1%; 95% CI 12.3%–16.1%) and sheep meat (p-estimate = 11.0%; 95% CI 3.6%–29.1%). The animal food products with the lowest prevalence of Campylobacter spp. were milk and dairy products (p-estimate = 3.5%; 95% CI 1.8%–6.5%), eggs (p-estimate = 4.0%; 95% CI 1.4%–10.7%), sausage (p-estimate = 9.4%; 95% CI 3.3%–24.0%), This meta-analysis concluding that C. jejuni is the most prevalent species worldwide and broiler meat is the main contamination source for human. The prevalence of Campylobacter species has public health importance and national authorities must monitor the situation in each country with the aim to establish the appropriate risk management measures.